The influence of a native english speaking environment on the pronunciation of efl brazilian speakers :: a study of the suprasegmentals - Garcia, Iria Werlang (2012)
Tese (Doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão.